All the white spaces : a novel - Wilkes, Ally (Emily Bestler Books/Atria, 2022)
"Something deadly and mysterious stalks the members of an isolated polar expedition in this haunting and spellbinding historical horror novel. In the wake of the First World War, Jonathan Morgan stows away on an Antarctic expedition, determined to find his rightful place in the world of men. Aboard the expeditionary ship, Jonathan may live as his true self--and true gender--and have the adventures he has always been denied. When disaster strikes in Antarctica's frozen Weddell Sea, the men must take to the land and overwinter somewhere which immediately seems both eerie and wrong; a place not marked on any of their part-drawn maps of the vast white continent. Now completely isolated, the expedition has no ability to contact the outside world. And no one is coming to rescue them. In the freezing darkness of the Polar night, where the aurora creeps across the sky, something terrible has been waiting to lure them out into its deadly landscape...As the harsh Antarctic winter descends, this supernatural force will prey on their deepest desires and deepest fears to pick them off one by one. It is up to Jonathan to overcome his own ghosts before he and the expedition are utterly destroyed"--